FOOD INSECURITY and MALNUTRITION of AFRICA: A COMBINED ATTEMPT CAN REDUCE THEM - Mohajan, Haradhan Kumar (Journal of Economic Development, Environment and People, 2022)
In the 21st century Africa is in the top levels of hunger and malnutrition in the world that is unharmonious with the vision of the African Union. Hunger and malnutrition is a common matter in almost all African countries and recently it is appeared to be increasing in most of the countries of the continent. Security of food and nutrition is a fundamental right of every people. But many people of Africa are deprived from this right. About one-third of African children is undersized in their growth and suffers from various physical and mental complexities. The UN Sustainable Development Goal (SDG) 2 aims to end all forms of hunger and malnutrition globally by 2030, but Africa is off track. It is estimated that about 200 million people of Africa are undernourished. Recently, the COVID-19 pandemic has worsened the African food and nutrition security system in the long-term. The pandemic has thrown the continent in serious uncertainty to the implementation of the SDG 2. Food production of this continent should be increased with the proportional to the increased populations. This study tries to discuss the food and nutrition situation of Africa and provides a constructive guideline to overcome it.